1997
DOI: 10.1080/000368497326525
|View full text |Cite
|
Sign up to set email alerts
|

Monetary stability and interest-free banking: the case of Iran

Abstract: Previous research has suggested that Islamic banking systems may be more stable than Western systems. However, this contention has only been tested empirically for the case of Tunisia, a country with no significant history of Islamic banking. This paper replicates the study done on Tunisia for the case of Iran, a country with some history of Islamic banking. The results are mixed, with some evidence both for and against the hypothesis of greater stability for Islamic banking. It is suggested that a good deal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…Conversely, Bjorvatn (1998), Kuran (1995Kuran ( , 2004 as well as Yusof and Wilson (2005) have highlighted the fact that the Islamic finance principles have handicapped the development of the economic activity. Other economists such as Darrat (1988), Yousefi et al (1997), Furqani and Mulyany (2009), Ammar et al (2013) have reached the result that the impact of the Islamic finance on the economic activity has turned out to be ambiguous and that there are no proofs of the superiority of the interest-free financial system over the interest-based one.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Bjorvatn (1998), Kuran (1995Kuran ( , 2004 as well as Yusof and Wilson (2005) have highlighted the fact that the Islamic finance principles have handicapped the development of the economic activity. Other economists such as Darrat (1988), Yousefi et al (1997), Furqani and Mulyany (2009), Ammar et al (2013) have reached the result that the impact of the Islamic finance on the economic activity has turned out to be ambiguous and that there are no proofs of the superiority of the interest-free financial system over the interest-based one.…”
Section: Introductionmentioning
confidence: 99%
“…The Islamic financial system, and experimental studies to date have been conducted to examine the efficiency and superiority and stability in Islamic banks as compared to conventional banks to achieve some milestones cash the ultimate goal that focuses towards the sustainability of real economic growth, reducing inflation and reducing unemployment. (Dara, 1988) found that the banking system, without the benefits of a more superior to the goal of cash found in the interim (Yousefi et al, 1997), and (Joseph and Wilson, 2005) there is no evidence superiority and stability of the system of interest free banking system compared to the Bank interest menu. Integrated depth and according to (Abdoulie 1991, the Cave, Ahmad and actually Hammoud, 1998, my friend, in 2002, Iqbal 1997) and to maximize profitability is not the only concern of the institutes of the Islamic banking and principles based on Islamic banks in the moral and ethical values.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although Islamic banks have been developed quite recently, there have been a number of theoretical and empirical studies that investigate the implications of these banks, especially comparing with the conventional interest-based banks in terms of its performance (see Khan [1985], Hassoune [2002], Darrat [2002], Youse… et al [1997], Yusof and Wilson [2005], Darrat [2002], and Isa and Kaleem [2006]). There are a few empirical studies that explore the relation between the Islamic banking system and growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…SeeKhan [1985],Darrat [2002],Youse… et al [1997],Hassoune [2002],Yusof and Wilson [2005],Isa and Kaleem [2006],Furqani and Mulyany [2009],Abduh and Chowdhury [2012], andGoaied and Sassi [2012].…”
mentioning
confidence: 99%